Komunikasi Visual: Analisis Semiotika Terhadap Baliho Calon Anggota Legislatif di Aceh Barat Tahun 2024 - Syahrani, Rizky Amalia; Dony Arung Triantoro; Raudhatun Nafisah; Ainal Fitri; Muhammad Haekal (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2024)
The 2024 general election in West Aceh District has brought interesting phenomena, particularly regarding the use of speech billboards with certain identities inserted by legislative candidates. This paper aims to analyze the factors underlying the dysfunction of these billboards. This research employs a qualitative methodology in the form of a case study. The data was collected from the documentation of billboards that were installed prior to the commencement of the campaign period in October 2023. The data were subjected to analysis through several stages based on the social semiotic analysis method, which was developed by Theo Van Leeuwen and comprises four dimensions: discourse, genre, style, and modality. Based on the social semiotic analysis of the speech billboards of legislative candidates in West Aceh, it can be concluded that the choice of language and visualization on speech billboards is used to promote personal identity. The use of speech billboards at weddings, graduation ceremonies, and religious events can be seen as a manifestation of the tendency to use religious sentiment for one's own political gain, with the potential to disrupt the sanctity of the event and the space in which the event takes place. The visualization that the legislative candidates want to convey is visual, by displaying photos and identities that are significantly larger than the event organizer, showing that there is power for the billboard owner, in this case the legislative candidates, to present themselves.